SEED VIABILITY AND GROWTH OF CACAO PLANT (Theobroma cacao L.) SEEDLINGS SULAWESI 01 AND ICCRI 08 CLONES - Maghfiroh, Canggih Nailil; Malik, Amalia (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2024)
Cocoa is one of the important agricultural commodities for various industrial activities such as cosmetics and food. Cocoa is widely consumed by the community, both in the form of instant chocolate and cocoa powder. Cocoa productivity is under its potential productivity, and have to enhance the cocoa production. The selection of clones for cocoa planting materials could determines the results of the plant. Plants convey genetic traits that can determine production capacity. Seedling viability and growth are indicators to determine whether plants can grow adeptly. Cocoa clones Sulawesi 01 and ICCRI 08 are superior clones that have the advantage of high productivity and are resistant to pests and diseases. The purpose of the study was to determine the viability of seeds and the growth of two cocoa clones Sulawesi 01 and ICCRI 08. The study design was a Completely Randomized Design with 2 levels and each had replications. The results of this study showed that the ICCRI 08 clone had the highest germinability of 92.1% and further the seedling growth parameters with a height of 6.6 cm at 21 days after planting. The highest vigor index measurement of 426.4 was in the ICCRI 08 clone and was significantly different compared to the Sulawesi 01 clone. The sigmoid curve showed the presence of growth initiation and exponential phases as indicated by increased growth as the plant age increased.